PENGEMBANGAN LITERASI MEMBACA: STRATEGI MENINGKATKAN MINAT BACA SISWA - Rani Noeraeni; Enok Munawaroh; Masruri Masruri; Nur Rahmad Yahya Wijaya; Rasuki Rasuki (JIP: Jurnal Ilmu Pendidikan, 2025)
Technological advances which result in children being lazy about reading books and preferring to play games on gadgets have a very bad impact on the intelligence of the nation's children. Reading is one of the most difficult things for many people, including children. Reading is essential for success in education. The benefits of reading are increasing intelligence and having broad insight, training critical thinking, improving memory and concentration. This research uses a qualitative descriptive method, with literature review collection techniques. Literature review is scientific writing which includes identification, reading relevant research, taking notes, making summaries, conducting library research, and writing general opinions. The aim of this research is to determine the importance of reading literacy and the strategies used to increase reading interest. The results of the research are the strategies used to increase interest in reading in 3 stages, namely the habituation stage, development stage and learning stage. The inhibiting factors in its implementation are lack of motivation from teachers so that students become lazy, limited funds which result in a lack of adequate facilities and infrastructure.